Analisis Kualitas Pelayanan Kebersihan Lingkungan di Kelurahan Cipedak Kecamatan Jagakarsa Kota Administrasi Jakarta Selatan - Indah Wahyu Maesarini; Sukini Sukini (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2016)
This study was conducted to determine Environmental Sanitation Services Quality Analysis in the Village of Cipedak Jagakarsa District South Jakarta Administration Municipality. This study using interviews with key informants (key informants), such as the Secretary of the Village Cipedak, Staff Village Cipedak, consultative council Village (LMK RW 04), Chairman of the Pillars of Citizens (RW 06), Chairman of the Pillars Stairs (RT 01 RW 05), Public figure, and PPSU With the question of Tangibles), Reliability, Responsiveness, Assurance, and Empathy.Service quality theory of Fitzsimmons (in Sedarmayanti, 2014: 276), namely: Tangibles, Reliability, responsiveness, Assurance, and Empathy. Based on the research results can be the result of: Tangibles, less distribution provision of bins in the form of a trash can, unavailability germor in RW 01 and RW 03 and the capacity germor amount that needs to be added on other RW, as well as the number of working equipment that is still lacking in support of the task of cleaning services.Responsiveness, responsiveness PPSU is good enough in responding to the waste problem that occurred in the Village Cipedak. It is shown from the complaints of citizens about the waste that is delivered swiftly and deftly PPSU officers immediately respond or respond to citizen complaints. Assurance, the findings indicate the presence of obstacles in the phase lug and garbage collection appear to have aligned between the community and officers PPSU in terms of collecting garbage in Shelter Trash (TPS) Meanwhile, of which there are still people who throw garbage at polling stations outside schedule determined so that it still looks rubbish in TPS are not finished transported. Empathy, PPSU officers in street litter attention to cleanliness is good enough, but the drains/river is still not optimal in handling. Reliability (reliability), is technically handling the problem of garbage in drains/river, but not right in accordance with the manner and method in cleaning up the garbage that was in the drains/river.